(untitled) (Observatorio Económico, 2011)
Approval of the Hidroaysén project now appears to be a settled fact, and for many there remains the sense of a debate that never took place. The project has a long history. There was a first attempt at processing it that considered the dams and the transmission line jointly. That project was withdrawn, and it was decided to seek approval for the dams and for the transmission line separately. Continue reading...